2015
DOI: 10.3171/2014.10.spine131089
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization with the Dynamic Cervical Implant: a novel treatment approach following cervical discectomy and decompression

Abstract: OBJECT Although cervical total disc replacement (TDR) has shown equivalence or superiority to anterior cervical discectomy and fusion (ACDF), potential problems include nonphysiological motion (hypermobility), accelerated degeneration of the facet joints, particulate wear, and compromise of the mechanical integrity of the endplate during device fixation. Dynamic cervical stabilization is a novel motion-preserving concept that facilitates controlled, limited flexion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
0
23
1
1
Order By: Relevance
“…Mackiewicz et al confirmed in a finite element study that introducing highly stiff stabilizing plates into cervical spine motion segments increases stress in the endplate of adjacent segments and that plates that allow greater range of motion show up to 30% reduction of adjacent plates resulting stress . Matge et al discussed clinical and radiological observations that suggest dynamic cervical implants as a promising alternative to total disc replacement, anterior cervical discectomy and spinal fusion, and they indicate that preserving motion segment biomechanics reduces stress on facet joints and development of adjacent segment disease. The advantage of our combined approach over existing interbody cage designs and dynamic cervical prosthetics remains in that our TE‐IVD has been shown to remodel over time and mature to restore mechanical function of spine segments to native conditions, when stably implanted and fully engrafted …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mackiewicz et al confirmed in a finite element study that introducing highly stiff stabilizing plates into cervical spine motion segments increases stress in the endplate of adjacent segments and that plates that allow greater range of motion show up to 30% reduction of adjacent plates resulting stress . Matge et al discussed clinical and radiological observations that suggest dynamic cervical implants as a promising alternative to total disc replacement, anterior cervical discectomy and spinal fusion, and they indicate that preserving motion segment biomechanics reduces stress on facet joints and development of adjacent segment disease. The advantage of our combined approach over existing interbody cage designs and dynamic cervical prosthetics remains in that our TE‐IVD has been shown to remodel over time and mature to restore mechanical function of spine segments to native conditions, when stably implanted and fully engrafted …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Mackiewicz et al confirmed in a finite element study that introducing highly stiff stabilizing plates into cervical spine motion segments increases stress in the endplate of adjacent segments and that plates that allow greater range of motion show up to 30% reduction of adjacent plates resulting stress. 33 Matge et al 34 discussed clinical and radiological observations that suggest dynamic cervical implants as a promising alternative to total disc replacement, anterior cervical discectomy and spinal fusion, and they indicate that preserving motion segment biomechanics reduces stress on facet Figure 3D), since the inclined shape of the endplate in the ventral side combined with the lack of anchoring for the implant resulted in a wedge-like extrusion. These observations were consistent with the mechanism of extrusion observed in the displaced implants of our in vivo canine study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro biomechanical testing 23 showed that the DCI has an intermediate place biomechanically between fusion and TDR. Restricted axial rotation and lateral bending protect the facet joints from extensive stress.…”
Section: Discussionmentioning
confidence: 99%
“…Auch ein dynamisches Implantat ist unter der Vorstellung der Reduktion der Re-Operationen wegen ASD entwickelt worden. Bislang liegen allerdings keine ausreichenden Daten vor, die die Überlegenheit dieses Implantats im Vergleich zur ACDF gezeigt haben [8].…”
Section: Anschlussdegeneration (Asd) Bandscheibenprothese Und Dynamiunclassified